Application of Technology in Health Administration: Perspectives of Hospital Administrative Staff in a Qualitative Context - Ana Faizah; Renny Sinaga; Teddy Tjahyanto (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the responses of administrative staff towards the implementation of the Hospital Management Information System (SIMRS) as part of the digital transformation in the healthcare sector. Using a descriptive qualitative approach, this research explores the experiences, perceptions, and challenges faced by staff in using information technology in hospital administrative activities. The findings indicate that the success of SIMRS implementation is heavily influenced by individual factors such as technological skills, age, and work experience, as well as organizational support such as adequate training and infrastructure. Although most staff recognize the benefits of efficiency and data accuracy offered by the technology, barriers such as resistance to change and limitations in facilities remain key challenges. This study provides valuable insights for hospital management in designing more effective technology implementation strategies that are user-centered.